Corrosion behavior of AlSi10Mg alloy produced by laser powder bed fusion under chloride exposure. (15th May 2019) - Cabrini, M.; Lorenzi, S.; Pastore, T.; Testa, C.; Manfredi, D.; Lorusso, M.; Calignano, F.; Pavese, M.; Andreatta, F.
Highlights: Corrosion resistance of as-built AlSi10Mg lower than that of polished samples. Chloride concentration played a key role in the initiation of localized corrosion. Selective dissolution of the α-Al phase observed, especially at melt pool edges. Si-rich particles acted as cathodes to promote preferential attack of Al. Abstract: Potentiodynamic tests were performed on AlSi10Mg alloy produced using laser powder bed fusion. As corrosion depends on the surface conditions, we compared the rough as-built surface with that formed after mechanical polishing and passivation in air. The as-built samples showed lower pitting potentials than polished samples. Corrosion initiation depended heavily on the chloride concentration. The higher potential of Si particles compared to the Al matrix provided the driving force for selective dissolution of the α-Al phase. The potential difference between the Si particles and α-Al phase was higher at the melt pool edges, resulting in preferential attack of these regions.